THE PROBLEMS OF ECOLOGY IN HIGH SCHOOL SYSTEM - Taylanov, Nizom (Физико-технологического образование, 2022)
As we know that the children is sensitive to the world around his and is in close contact with it, especially at a young age. As he grows up, the child loses this connection, acquiring the habits of the consumer society. It is therefore important to form in the child an understanding of the world around him and the need to care for him. This is especially effective in schools